2019
DOI: 10.21533/pen.v7i1.355
|View full text |Cite
|
Sign up to set email alerts
|

Emotions identification utilizing periodic handwriting on mobile surfaces

Abstract: The purpose of this study is to between the learners' emotional characteristics and styles in touch screen environments. We propose a method to identify the variety of learners' boredom in the learning process utilising handwriting data. The novelty of the method is to avoid explicit polling of learners how do they feel. We use the recurring acquiring of personal handwriting data utilising the computational power of both a mobile device and cloud-based resources. Also, we use machine learning-based sentiment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Thus, the applied teaching materials were not appropriate for the learners. Zagorskis et al (2019) suggested that teachers should find a solution for learners' boredom.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the applied teaching materials were not appropriate for the learners. Zagorskis et al (2019) suggested that teachers should find a solution for learners' boredom.…”
Section: Resultsmentioning
confidence: 99%
“…Large taxpayers require special tax attention which has resulted in introducing specified offices for large taxpayers in the structure of fiscal services. In addition to the study conducted on taxation subjects' tax consciousness, it is also defined as either a form of behavior, or emotions that arise in the process of taxation [23], [36], which, in our opinion, is one-sided. Tax consciousness is evaluated as a factor of fulfilling the tax duty conscientiously [23], or as a result of fulfilling the tax duty [15].…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive component [2], [5], [8], [10], [12] Emotional & volitional component [1], [2], [3], [4], [11], [36] Behavioral component [6], [19] The first level of the hierarchy represents the objectives of evaluating the components of tax consciousness: cognitive K, emotional-volitional E, and behavioral P ones. The second level includes factors determining the previous level components, namely: tax awareness, emotions that arise in the process of taxation, attitude to taxation, guidelines on how to act in terms of taxation.…”
Section: Tax Consciousness Evaluation 1 Hierarchy Level: Aimsmentioning
confidence: 99%
“…On the other hand, the keyboard layout is designed for inputting English letters, for people whose native language is not English, they may find it is not easy to use, instead, writing on a touchscreen may be much easier than typing on a normal keyboard. Therefore, in the future, writing on a touchscreen may give users similar experience as writing in paper with a pen or brush [115,116]. For example, combining the traditional calligraphy with modern digital art provides a new way to create, present and preserve calligraphy works.…”
Section: E Recognizing Emotions Through Digital Writingmentioning
confidence: 99%